Preliminary experience with the use of ultra-low profile endografts - Mazzaccaro, Daniela (Diagn Interv Radiol, 2017)
PURPOSE: We aimed to report a preliminary single-center experience of elective endovascular aortic repair (EVAR) using ultra-low profile (ULP) endografts of 14 F outer diameter. METHODS: Data of 67 consecutive patients who underwent EVAR using either Ovation (group A, n=30) or Incraft (group B, n=37) endografts were retrospectively analyzed. RESULTS: Aorto-iliac anatomy was significantly different between the two groups, as patients of group A had a greater thrombotic apposition on proximal aortic neck (thrombus thickness: 7.2±1 mm vs. 3.3±1.6 mm, P = 0.042; percentage of the circumference covered by thrombus: 45.2%±10.4% vs. 18.7%±10.6%, P = 0.0003), while patients of group B had a more angulated proximal neck in the coronal axis (35.9°±6.4° vs. 16.7°±5°, P = 0.012). Procedural success was 93.3% and 97.3%, respectively, in groups A and B. One patient in group A required an immediate conversion to open surgery for persistent occlusion of both iliac limbs. Another patient required implantation of a conical endograft with a femoro-femoral right-to-left bypass for occlusion of the contralateral gate during the cannulation. In group B, one intraoperative type Ia endoleak was immediately corrected. Neither deaths nor major adverse events were recorded within 30-days. During a median follow-up of 15.2 months (range, 1–56.7 months) two type Ia endoleaks in group A required open conversion after 12.1 and 40.5 months, respectively. Three patients in group B required a reintervention after 30 days. Neither deaths nor aortic ruptures were recorded during follow-up. CONCLUSION: Both ULP endografts showed satisfying early and mid-term results.